Pengembangan Instrumen Tes Untuk Mengukur Kemampuan Konsep Dasar Mata Kuliah Statistik - Sahrul Sahrul; Lisa Virdinarti Putra; Sudarsono Sudarsono; Reza Fahlefi; Anton Afries Setyawan (Jurnal Tematik, 2025)
This research aims to develop valid and reliable test instruments aligned with the learning outcomes of the statistics course. This test instrument serves as a learning evaluation tool to measure students' ability to solve statistical problems, both in formative and summative assessments. This research is a development research model using nine stages: 1) developing test specifications, 2) writing test items, 3) reviewing test items, 4) conducting test trials, 5) analyzing test item scores, 6) revising the test, 7) assembling the test, 8) administering the test, and 9) interpreting the test results. This research was conducted on Early Childhood Education students at W Central Java University, with a sample size of 31 people. This study used evaluation, observation, interviews, and tests to determine students' ability to solve statistical problems related to finding class intervals in grouped data. Based on the analysis results using the Jamovi application, the test instrument developed to measure students' abilities in the Statistics course has met the criteria. The quality of the instrument is valid and reliable, with a value greater than (>) 0.3. Based on the results of students' knowledge answers calculated using the learning outcomes percentage formula, the average score is 72.6%, which falls into the high category.